Personality dimensions and academic procrastination in students of online courses at a Peruvian university - Charaña Mamani, José (2021)
The present research aimed to determine the relationship between the dimensions of personality and academic procrastination, in addition to describing the levels of procrastination according to age and sex in students of online courses at a Peruvian university in the city of Tarapoto, 2020. The type of investigation was of non-experimental transversal design of correlational type, of non-probability sampling for convenience, the sample was confirmed by 240 university students whose ages oscillated between 16 and 40 years (66.3% females and 33.7% males; mean age = 20.66). The instruments used were the academic procrastination scale (EPA) and the Big Five Inventory-15P (BFI-15P). The results revealed a significant inverse correlation between the dimensions of personality and academic procrastination; responsibility (rho= -0.590; p < .001), kindness (rho= -0.457; p < .000), extraversion (rho= -0.226; p< .000) and openness (rho= -355; p< .000); it means that the greater the responsibility, kindness, extraversion and openness the less academic procrastination will be or vice versa. The opposite happens with the neuroticism dimension, which presents a significant direct correlation (rho= 0.166; p < .000), so that the greater the neuroticism, the greater the academic procrastination.